PIF1 helicase promotes break‐induced replication in mammalian cells. (20th January 2021) - Li, Shibo; Wang, Hailong; Jehi, Sanaa; Li, Jun; Liu, Shuo; Wang, Zi; Truong, Lan; Chiba, Takuya; Wang, Zefeng; Wu, Xiaohua
Abstract: Break‐induced replication (BIR) is a specialized homologous‐recombination pathway for DNA double‐strand break (DSB) repair, which often induces genome instability. In this study, we establish EGFP‐based recombination reporters to systematically study BIR in mammalian cells and demonstrate an important role of human PIF1 helicase in promoting BIR. We show that at endonuclease cleavage sites, PIF1‐dependent BIR is used for homology‐initiated recombination requiring long track DNA synthesis, but not short track gene conversion (STGC). We also show that structure formation‐prone AT‐rich DNA sequences derived from common fragile sites (CFS‐ATs) induce BIR upon replication stress and oncogenic stress, and PCNA‐dependent loading of PIF1 onto collapsed/broken forks is critical for BIR activation. At broken replication forks, even STGC‐mediated repair of double‐ended DSBs depends on POLD3 and PIF1, revealing an unexpected mechanism of BIR activation upon replication stress that differs from the conventional BIR activation model requiring DSB end sensing at endonuclease‐generated breaks. Furthermore, loss of PIF1 is synthetically lethal with loss of FANCM, which is involved in protecting CFS‐ATs. The breast cancer‐associated PIF1 mutant L319P is defective in BIR, suggesting a direct link of BIR to oncogenic processes. SYNOPSIS: Break‐induced replication (BIR) mediates recombination where DNA strand homology is limited to one end of donor sequence. Here, the helicase PIF1 is found to play a critical BIR role in mammalian cells coping with replication stress. An EGFP‐based reporter allows monitoring BIR in mammalian cells. Loss of PIF1 or its helicase activity reduces BIR frequency at induced double‐strand breaks (DSBs). BIR activation is controlled differently at DSBs generated by endonucleases versus those caused by replication fork breakage. PIF1 protects structure‐prone AT‐rich sequences derived from common fragile sites, and its loss is syntheticaly lethal in absence of FANCM. Cells expressing the breast cancer‐associated PIF1‐L319P mutant are defective in BIR. Abstract : BIR‐mediated homologous recombination allows mammalian cells to cope with replication stress and is differently controlled at fork‐breakage‐induced vs endonucleases‐generated DSBs.